CHARACTERIZATION OF THE SPYTAG - SPY-CATCHER INTERACTION - Ludwig, Jonas; Ulm, Nadine; Pröschel, Marlene; Sticht, Heinrich; Sonnewald, Uwe; Eichler, Jutta (Journal of Peptide Science, 2016)

Self-assembly of supramolecular architectures and polymers by orthogonal metal complexation and hydrogen-bonding motifs - Grimm, Felix; Ulm, Nadine; Gröhn, Franziska; Düring, Jasmin; Hirsch, Andreas (Chemistry - A European Journal, 2011)
A modular construction kit with two orthogonal noncovalent binding sites for self-assembly of supramolecular architectures is presented. The heteroditopic building blocks contain a terpyridine (tpy) unit for coordination of metal ions and a Hamilton receptor for multiple H-bonding of cyanuric acid derivatives. The association constants of ligand binding of M complexes (M=Ru, Zn, Fe, and Pt) with a dendritic end cap were determined to be in the range of 10 and 10 L mol in chloroform. The capabilities for binding of metal ions were investigated by H NMR and UV/Vis spectroscopy. The Fe complexes are most appropriate for the generation of discrete and high-ordered architectures due to their strong tendency to form FeL complexes. Superstructures are readily formed in a one-pot procedure at room temperature. No mutual interactions between the orthogonal binding motifs were observed, and this demonstrates the highly specific nature of each binding process. Decomplexation experiments were carried out to examine the reversibility of Fe-tpy coordination. Substitution of the terminal end cap with a homoditopic bis-cyanurate linkage leads to formation of an iron-containing supramolecular strand. Formation of coordination polymers was confirmed by viscosity measurements. The supramolecular polymer strands can be reversibly cleaved by addition of a terminating cyanuric acid building block, and this proves the dynamic nature of this noncovalent polymerization process. Copyright © 2011 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.